New roles for the BLyS/BAFF family in antigen-experienced B cell niches - Goenka, Radhika; Scholz, Jean L.; Sindhava, Vishal J.; Cancro, Michael P. (Cytokine & growth factor reviews, 2014)
BLyS family members govern selection and survival of cells in the pre-immune B cell compartment, and emerging evidence suggests similar roles in antigen-experienced B cell pools. We review the features of this family, with particular emphasis on recent findings of how BLyS influences affinity maturation in germinal centers, which lie at the intersection of the pre-immune and antigen-experienced B cell compartments. We propose a model whereby tolerogenic selection at the transitional stage and affinity maturation in the germinal center employ the same BLyS driven mechanism.